Bibliometric analysis and visualization mapping of herpes zoster vaccine publications from 1999 to 2024 - Gao, Wenli; Gao, Dongyang; Li, Lin; Li, Juan; Yao, Xinyi; Zhang, Junling (Frontiers in Medicine, 2025)
BackgroundHerpes Zoster (HZ) is a viral skin disease caused by reactivation of latent Varicella Zoster Virus (VZV) in human ganglia, presenting with unilateral neuropathic pain and vesicular rash. HZ imposes significant burden on patients and healthcare systems, often complicated by postherpetic neuralgia (PHN). The live attenuated zoster vaccine (ZVL, Zostavax) reduces HZ risk by 51% and PHN by 65% in adults ≥60 years. The recombinant zoster vaccine (RZV, Shingrix) shows approximately 90% efficacy in adults ≥50 years. Despite withdrawal of Zostavax from the U.S. market, RZV uptake remains suboptimal due to vaccine hesitancy and provider knowledge gaps. This study aims to analyze global research trends on HZ vaccines using bibliometric methods.MethodsPublications on “herpes zoster” and “zoster vaccine” were retrieved from the Web of Science Core Collection (WoSCC) database (1999–2024). Bibliometric and visualization tools including CiteSpace, VOSviewer, and R-bibliometrix were applied to analyze contributions by countries, institutions, journals, authors, references, and keywords.ResultsA total of 719 articles from 261 journals across 56 countries were included. The United States led publications, with GlaxoSmithKline (GSK) as the most prolific institution. Vaccine was the most prolific journal; Levin et al. was the most productive author. The most cited article, “Efficacy of the Herpes Zoster Subunit Vaccine in Adults Aged 70 Years or Older,” by Cunningham AL, appeared in the New England Journal of Medicine. Frequently used keywords included “herpes zoster,” “vaccination,” “postherpetic neuralgia,” “efficacy,” “subunit vaccine,” and “safety”.ConclusionThis bibliometric study comprehensively summarizes HZ vaccine research over 25 years, offering insights to guide future research and clinical practice.